Adhesive capable of inhibiting electromagnetic interference
By adding nitrogen-doped activated carbon material loaded with iron oxide to the epoxy resin adhesive, the problem of insufficient shielding of epoxy resin adhesive in electromagnetic interference test is solved, and effective suppression of electromagnetic interference and electromagnetic shielding performance is achieved. The improvement extends the service life of electronic equipment.
Patent Information
- Application Number
- CN202411611006.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing epoxy resin adhesives are difficult to meet electromagnetic shielding requirements in electromagnetic interference (EMI) testing, which affects the service life of electronic equipment.
Using nitrogen-doped activated carbon material loaded with iron oxide as carbon-based functional additives, it enhances the electromagnetic shielding performance of epoxy resin adhesives, combined with specific raw material ratios and preparation methods An adhesive with excellent electromagnetic shielding effect was prepared.
Effectively suppress electromagnetic interference, significantly improve the electromagnetic shielding performance of epoxy resin adhesives, meet the EMI testing needs, and extend the service life of electronic equipment.
Smart Images

Figure CN119242238A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adhesives, and in particular to an adhesive capable of suppressing electromagnetic interference. Background Art
[0002] With the rapid development of science and technology, electronic devices have become an indispensable part of our daily lives. From smartphones, tablets to wearable devices, to automotive electronics and aerospace systems, the performance and reliability requirements of electronic equipment are increasing. In the manufacturing process of these devices, adhesives, as an important connection material, play a vital role. They are not only used to fix and seal structural parts, but also undertake multiple functions such as conductivity, heat conduction, insulation, and shock absorption. Among the many adhesive substrates, epoxy resin adhesives have more excellent corrosion resistance, acid and alkali resistance, impact resistance and other functionalities, and excellent temperature resistance. It can work stably in the temperature range of -60°C to 120°C. At the same time, it also has good electrical insulation properties to ensure the safety of electronic modules. Therefore, epoxy resin adhesives play an important role in electronic equipment. However, the electrical properties of epoxy resin adhesives, such as capacitance and inductance, may cause electromagnetic interference (EMI) test failures, resulting in malfunction of electronic devices during EMI testing and affecting the service life of electronic equipment. Therefore, improving the electromagnetic shielding performance of epoxy resin adhesives is of great significance for their application in electronic equipment.
[0003] At present, the electromagnetic shielding effect of epoxy resin adhesive is generally improved by adjusting the components of the adhesive, for example, dielectric materials or high magnetic permeability inductor materials are integrated into the adhesive, and electromagnetic interference is suppressed by changing the resonant frequency or absorbing electromagnetic energy. However, the above-mentioned existing materials are difficult to meet the electromagnetic shielding requirements required for EMI testing. Based on this, the present invention provides an epoxy resin adhesive with good electromagnetic shielding effect, which can effectively suppress electromagnetic interference. Summary of the invention
[0004] 1. Technical issues to be resolved In view of the deficiencies of the prior art, the present invention provides an adhesive that can suppress electromagnetic interference.
[0005] (II) Technical solution An adhesive capable of suppressing electromagnetic interference comprises the following raw materials measured in parts by weight: 45-53 parts of epoxy resin; 3-4.5 parts of carbon-based functional additives; Defoaming agent 0.5-1.5 parts; 10-15 parts of diluent; Thixotropic agent 0.5-1 part; 5-15 parts of curing agent; 1-3 parts of curing accelerator.
[0006] As a further embodiment of the present invention, the preparation method of the adhesive comprises the following steps: Step 1: Prepare the ingredients Weigh each raw material according to its weight and set aside; Step 2: Mixing Add epoxy resin, diluent and thixotropic agent into a mixer, stir mechanically at a stirring rate of 1000-2000 r / min to mix evenly, then add carbon-based functional additives into the mixer and stir evenly, then adjust the stirring rate to 200-300 r / min, continue to add curing agent and curing accelerator into the mixer, stir mechanically for 10-30 minutes to form a mixture; Step 3: Defoaming Add defoamer to the mixture, continue stirring for 20-30 minutes, let it stand for 1-2 hours, and then discharge the mixture to obtain the adhesive.
[0007] As a further embodiment of the present invention, the epoxy resin is any one of bisphenol A epoxy resin and bisphenol F epoxy resin.
[0008] As a further embodiment of the present invention, the preparation method of the carbon-based functional additive is specifically as follows: After the xylan modified complex and the pore-forming agent are ground and mixed evenly, they are placed in a tubular furnace for calcination, and the heating rate is controlled to be 3-5°C / min. Under nitrogen protection conditions, the temperature is gradually increased to 700-750°C. After calcination for 1-3 hours under this temperature condition, the nitrogen is removed, the heating is stopped, the temperature is lowered and the material is discharged. After washing and vacuum drying, a carbon-based functional additive can be obtained.
[0009] As a further embodiment of the present invention, the method for preparing the xylan modified complex specifically comprises the following steps: Step 1, add xylan and tetrahydrofuran to a reactor filled with nitrogen, start stirring, and after a uniform reaction liquid is formed, add chlorogenic acid to the reaction liquid. After the addition is completed, add the composite catalyst to the reaction liquid under ice bath conditions. After the addition is completed, remove the ice bath, mechanically stir at room temperature for 4-8 hours, evaporate the solvent, cool and discharge the material, and obtain modified xylan; Step 2: Add the modified xylan to 70-80% ethanol by volume, start stirring, and after it is completely mixed, add metal salts, stir and disperse evenly, adjust the pH to 7-9, then keep stirring at 40-45°C for 1-3h, cool and discharge, and you can get a xylan modified complex.
[0010] As a further solution of the present invention, in step 1, the composite catalyst is a mixture of a condensation agent and a promoter, and the mass ratio is 1:0.3-0.4.
[0011] As a further embodiment of the present invention, the condensing agent is dicyclohexylcarbodiimide or 1-ethyl-(3-dimethylaminopropyl)carbodiimide; and the accelerator is N-hydroxysuccinimide or 4-dimethylaminopyridine.
[0012] As a further embodiment of the present invention, in step 2, the metal salt substance is ferric nitrate or ferric sulfate.
[0013] As a further solution of the present invention, in step 2, the mass ratio of the xylan modified complex to the pore-forming agent is 1:2-4; and the pore-forming agent is zinc chloride.
[0014] In the above technical scheme, a composite catalyst is first used to catalyze the amidation condensation reaction between the amino group in the xylan structure and the active carboxyl substituent in the chlorogenic acid structure, thereby introducing a catechol structure into the xylan structure to obtain a modified xylan. Under alkaline conditions, the catechol structure can form a stable complex with iron metal ions to obtain a xylan modified complex complexing iron ions.
[0015] Finally, using xylan as the carbon source, nitrogen source and oxygen source, and the complexed iron element as the iron source, after activation pore making and high-temperature calcination, the xylan is calcined to form a nitrogen-doped activated carbon material, and the iron element combines with oxygen to form iron oxide, and finally a nitrogen-doped activated carbon material loaded with iron oxide, that is, a carbon-based functional additive, is obtained.
[0016] As a further embodiment of the present invention, the defoaming agent is BYK-A530 or BYK-A515; the diluent is any one of 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether or p-tert-butylphenyl glycidyl ether; and the thixotropic agent is fumed silica.
[0017] As a further solution of the present invention, the curing agent is polyetheramine; and the curing accelerator is an imidazole curing accelerator.
[0018] 3. Beneficial technical effects The carbon-based functional additive prepared by the present invention is a nitrogen-doped activated carbon material loaded with iron oxide. First, the nitrogen-doped activated carbon material has a large number of rich and uniform pore structures. This pore structure can achieve the purpose of absorbing electromagnetic waves by reflecting and scattering electromagnetic waves. The doping of nitrogen elements can produce defect structures in the activated carbon structure to form electric dipoles. The generation of these electric dipoles can effectively enhance the dielectric loss effect of the activated carbon material. In addition, the iron oxide loaded in the activated carbon material can effectively improve the magnetism of the activated carbon material, and also help to enhance the electromagnetic shielding effect of the activated carbon material. Therefore, adding the carbon-based functional additive to the epoxy resin matrix can effectively enhance the electromagnetic shielding performance of the prepared epoxy resin adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0020] Figure 1 This is a scanning electron microscope image of carbon-based functional additives. DETAILED DESCRIPTION
[0021] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. Preferred embodiments of the present invention are given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0022] Preparation Example 1 Preparation of carbon-based functional additives: Step 1, add 3.6g of xylan and tetrahydrofuran to a reactor filled with nitrogen, start stirring, and after a uniform reaction liquid is formed, add 0.5g of chlorogenic acid to the reaction liquid. After the addition is completed, add 0.2g of dicyclohexylcarbodiimide and 0.06g of 4-dimethylaminopyridine to the reaction liquid under ice bath conditions. After the addition is completed, remove the ice bath, mechanically stir at room temperature for 6h, evaporate the solvent, cool and discharge the material to obtain modified xylan; Step 2: Add 2.5 g of modified xylan to 70% ethanol by volume, start stirring, and after it is completely mixed, add 0.3 g of ferric sulfate, stir and disperse evenly, adjust the pH to 8, and then keep stirring at 40°C for 2 hours, cool and discharge the material to obtain a xylan modified complex; Step 3: Grind and mix 3g of xylan modified complex and 10g of zinc chloride evenly, place them in a tubular furnace for calcination, control the heating rate to 5°C / min, and gradually increase the temperature to 750°C under nitrogen protection. After calcination for 2h at this temperature, remove the nitrogen, stop heating, cool and discharge the material, wash and vacuum dry to obtain a carbon-based functional additive.
[0023] Figure 1 This is a scanning electron microscope image of the carbon-based functional additive. It can be observed that it has a rich porous structure and a large number of nano-scale particles are deposited on the surface. Analysis shows that the nano-scale particles are iron oxides, namely iron oxide.
[0024] Example 1 An adhesive capable of suppressing electromagnetic interference comprises the following raw materials measured in parts by weight: Epoxy resin 45 parts; 3 parts of carbon-based functional additives; Defoamer BYK-A530 0.5 parts; Diluent 1,4-butanediol condensed glycerol ether 10 parts; 0.5 parts of fumed silica; Curing agent polyetheramine 5 parts; 1 part of curing accelerator.
[0025] The preparation method of the adhesive comprises the following steps: Step 1: Prepare the ingredients Weigh each raw material according to its weight and set aside; Step 2: Mixing Epoxy resin, 1,4-butanediol condensed glycerol ether, and fumed silica were added to a mixer, and mechanically stirred at a stirring rate of 1000 r / min to mix them evenly. Then, the carbon-based functional additive was added to the mixer and stirred evenly. Then, the stirring rate was adjusted to 200 r / min, and the curing agent polyetheramine and the curing accelerator were continuously added to the mixer, and mechanically stirred for 30 minutes to form a mixture. Step 3: Defoaming Add defoamer BYK-A530 to the mixture, continue stirring for 20 minutes, let it stand for 1 hour, and discharge the mixture to obtain the adhesive.
[0026] The epoxy resin is E44 epoxy resin; the carbon-based functional additive is the carbon-based functional additive prepared in Preparation Example 1; the curing accelerator is heptadecyl imidazole, and the same applies to the following.
[0027] Example 2 An adhesive capable of suppressing electromagnetic interference comprises the following raw materials measured in parts by weight: Epoxy resin 50 parts; 4 parts of carbon-based functional additives; Defoaming agent BYK-A515 1 part; Diluent 1,6-hexanediol diglycidyl ether 12 parts; 0.6 parts of fumed silica; Curing agent polyetheramine 10 parts; 2 parts of curing accelerator.
[0028] The preparation method of the adhesive comprises the following steps: Step 1: Prepare the ingredients Weigh each raw material according to its weight and set aside; Step 2: Mixing Epoxy resin, 1,6-hexanediol diglycidyl ether, and fumed silica were added to a mixer, and mechanically stirred at a stirring rate of 1500 r / min to mix them evenly. Then, the carbon-based functional additive was added to the mixer and stirred evenly. Then, the stirring rate was adjusted to 300 r / min, and the curing agent polyetheramine and the curing accelerator were continuously added to the mixer, and mechanically stirred for 20 minutes to form a mixture. Step 3: Defoaming Add defoamer BYK-A515 to the mixture, continue stirring for 25 minutes, let it stand for 1 hour, and discharge the mixture to obtain the adhesive.
[0029] Example 3 An adhesive capable of suppressing electromagnetic interference comprises the following raw materials measured in parts by weight: Epoxy resin 53 parts; 4.5 parts of carbon-based functional additives; Defoamer BYK-A515 1.5 parts; 15 parts of diluent neopentyl glycol diglycidyl ether; 1 part of fumed silica; Curing agent polyetheramine 15 parts; 3 parts of curing accelerator.
[0030] The preparation method of the adhesive comprises the following steps: Step 1: Prepare the ingredients Weigh each raw material according to its weight and set aside; Step 2: Mixing Epoxy resin, neopentyl glycol diglycidyl ether, and fumed silica were added to a mixer, and mechanically stirred at a stirring rate of 2000 r / min to mix them evenly. Then, the carbon-based functional additive was added to the mixer and stirred evenly. Then, the stirring rate was adjusted to 300 r / min, and the curing agent polyetheramine and the curing accelerator were continuously added to the mixer, and mechanically stirred for 10 minutes to form a mixture. Step 3: Defoaming Add defoamer BYK-A515 to the mixture, continue stirring for 30 minutes, let it stand for 2 hours, and then discharge the mixture to obtain the adhesive.
[0031] Comparative Example 1 An adhesive capable of suppressing electromagnetic interference comprises the following raw materials measured in parts by weight: Epoxy resin 50 parts; 4 parts of commercially available activated carbon; Defoaming agent BYK-A515 1 part; Diluent 1,6-hexanediol diglycidyl ether 12 parts; 0.6 parts of fumed silica; Curing agent polyetheramine 10 parts; 2 parts of curing accelerator.
[0032] The preparation method of the adhesive comprises the following steps: Step 1: Prepare the ingredients Weigh each raw material according to its weight and set aside; Step 2: Mixing Epoxy resin, 1,6-hexanediol diglycidyl ether, and fumed silica were added to a mixer, and mechanically stirred at a stirring rate of 1500 r / min to mix them evenly. Commercially available activated carbon was then added to the mixer and stirred evenly. The stirring rate was then adjusted to 300 r / min, and a curing agent polyetheramine and a curing accelerator were continuously added to the mixer, and mechanically stirred for 20 minutes to form a mixture. Step 3: Defoaming Add defoamer BYK-A515 to the mixture, continue stirring for 25 minutes, let it stand for 1 hour, and discharge the mixture to obtain the adhesive.
[0033] The commercially available activated carbon was purchased from the first-grade bamboo charcoal of Anhui Xingheng Environmental Protection Technology Co., Ltd., with a fixed carbon content of ≥90.0%.
[0034] Comparative Example 2 An adhesive capable of suppressing electromagnetic interference comprises the following raw materials measured in parts by weight: Epoxy resin 50 parts; Defoaming agent BYK-A515 1 part; Diluent 1,6-hexanediol diglycidyl ether 12 parts; 0.6 parts of fumed silica; Curing agent polyetheramine 10 parts; 2 parts of curing accelerator.
[0035] The preparation method of the adhesive comprises the following steps: Step 1: Prepare the ingredients Weigh each raw material according to its weight and set aside; Step 2: Mixing Add epoxy resin, 1,6-hexanediol diglycidyl ether, and fumed silica into a mixer, stir mechanically at a stirring rate of 1500 r / min until uniformly mixed, adjust the stirring rate to 300 r / min, continue to add curing agent polyetheramine and curing accelerator into the mixer, stir mechanically for 20 minutes, and form a mixture; Step 3: Defoaming Add defoamer BYK-A515 to the mixture, continue stirring for 25 minutes, let it stand for 1 hour, and discharge the mixture to obtain the adhesive.
[0036] Test Case The adhesives in the embodiments and comparative examples were uniformly coated on the surface of the glass plate, and the coating thickness was controlled to be 50 μm. After coating, they were placed in an oven at 120° C. for curing. After they were completely cured, they were taken out, left to cool, and demolded to make test samples that met the specifications. The electromagnetic shielding performance test was carried out with reference to the standard MIL-DTL-83528C. The results are shown in the following table: Table 1 - Test results Analysis shows that by modifying the epoxy resin with the carbon-based functional additive in Preparation Example 1 of the present invention, the prepared epoxy resin adhesive can have an excellent electromagnetic shielding effect, thereby effectively suppressing electromagnetic interference.
[0037] Based on the ideal embodiment of the present invention, through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. An adhesive capable of suppressing electromagnetic interference, characterized in that: The following raw materials are included in parts by weight: 45-53 parts of epoxy resin; 3-4.5 parts of carbon-based functional additives; Defoaming agent 0.5-1.5 parts; 10-15 parts of diluent; Thixotropic agent 0.5-1 part; 5-15 parts of curing agent; 1-3 parts of curing accelerator.
2. The adhesive capable of suppressing electromagnetic interference according to claim 1, characterized in that: The preparation method of the adhesive comprises the following steps: Step 1: Prepare the ingredients Weigh each raw material according to its weight and set aside; Step 2: Mixing Add epoxy resin, diluent and thixotropic agent into a mixer, stir mechanically at a stirring rate of 1000-2000 r / min to mix evenly, then add carbon-based functional additives into the mixer and stir evenly, then adjust the stirring rate to 200-300 r / min, continue to add curing agent and curing accelerator into the mixer, stir mechanically for 10-30 minutes to form a mixture; Step 3: Defoaming Add defoamer to the mixture, continue stirring for 20-30 minutes, let it stand for 1-2 hours, and then discharge the mixture to obtain the adhesive.
3. The adhesive capable of suppressing electromagnetic interference according to claim 1, characterized in that: The epoxy resin is any one of bisphenol A epoxy resin and bisphenol F epoxy resin.
4. The adhesive capable of suppressing electromagnetic interference according to claim 1, characterized in that: The preparation method of the carbon-based functional additive is specifically as follows: After the xylan modified complex and the pore-forming agent are ground and mixed evenly, they are placed in a tubular furnace for calcination, and the heating rate is controlled to be 3-5°C / min. Under nitrogen protection conditions, the temperature is gradually increased to 700-750°C. After calcination for 1-3 hours under this temperature condition, the nitrogen is removed, the heating is stopped, the temperature is lowered and the material is discharged. After washing and vacuum drying, a carbon-based functional additive can be obtained.
5. The adhesive capable of suppressing electromagnetic interference according to claim 4, characterized in that: The preparation method of the xylan modified complex specifically comprises the following steps: Step 1, add xylan and tetrahydrofuran to a reactor filled with nitrogen, start stirring, and after a uniform reaction liquid is formed, add chlorogenic acid to the reaction liquid. After the addition is completed, add the composite catalyst to the reaction liquid under ice bath conditions. After the addition is completed, remove the ice bath, mechanically stir at room temperature for 4-8 hours, evaporate the solvent, cool and discharge the material, and obtain modified xylan; Step 2: Add the modified xylan to 70-80% ethanol by volume, start stirring, and after it is completely mixed, add metal salts, stir and disperse evenly, adjust the pH to 7-9, then keep stirring at 40-45°C for 1-3h, cool and discharge, and you can get a xylan modified complex.
6. The adhesive capable of suppressing electromagnetic interference according to claim 5, characterized in that: In step 1, the composite catalyst is a mixture of a condensation agent and a promoter, with a mass ratio of 1:0.3-0.
4.
7. The adhesive capable of suppressing electromagnetic interference according to claim 6, characterized in that: The condensing agent is dicyclohexylcarbodiimide or 1-ethyl-(3-dimethylaminopropyl)carbodiimide; and the accelerator is N-hydroxysuccinimide or 4-dimethylaminopyridine.
8. The adhesive capable of suppressing electromagnetic interference according to claim 5, characterized in that: In step 2, the metal salt substance is ferric nitrate or ferric sulfate.
9. The adhesive capable of suppressing electromagnetic interference according to claim 4, characterized in that: The mass ratio of the xylan modified complex to the pore-forming agent is 1:2-4; the pore-forming agent is zinc chloride.
10. The adhesive capable of suppressing electromagnetic interference according to claim 1, characterized in that: The defoaming agent is BYK-A530 or BYK-A515; the diluent is any one of 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether or p-tert-butylphenyl glycidyl ether; the thixotropic agent is fumed silica; the curing agent is polyether amine; and the curing accelerator is an imidazole curing accelerator.
Citation Information
Patent Citations
Preparation method of high-dispersion type conductive slurry
CN107910132A
Preparation method and application of nitrogen-doped biochar-loaded monatomic iron
CN112007681A
Adhesive with double functions of electromagnetic shielding and heat conduction for electronic packaging and preparation method of adhesive
CN114507497A
Solid inorganic / organic hybrid with modified surface
US20100226991A1
